Is There a Novelty Premium on New Financial Instruments? : The Argentine Experience with GDP-Indexed Warrants - Ricci, Luca (IMF Working Papers; Working Paper, 2008)
This paper examines the Argentine experience with GDP-indexed warrants in order to gauge the existence of a novelty premium on new financial instruments. It develops a Monte Carlo pricing exercise to calculate the expected net present value of payments, on the basis of various forecast assumptions. The results show that the residual premium paid by these warrants over standard bonds declined significantly by about 600 basis points between December 2005 and July 2007. This suggests that financial innovation may be associated with premia, which decay reasonably fast.